Potential Involvement of Jagged1 in Metastatic Progression of Human Breast Carcinomas. (6th January 2020) - Bednarz-Knoll, Natalia; Efstathiou, Antonia; Gotzhein, Frauke; Wikman, Harriet; Mueller, Volkmar; Kang, Yibin; Pantel, Klaus
Abstract: BACKGROUND: Jagged1, the ligand of Notch, has been shown to be involved in formation of bone metastases in an experimental study. Here, clinical relevance of Jagged1 expression in tumor progression was assessed in human breast carcinomas. METHODS: Jagged1 expression was evaluated by immunohistochemistry in 228 tumor tissue samples and compared to clinicopathologic parameters and patients' outcomes. Furthermore, circulating tumor cells (CTCs) from peripheral blood of 100 unmatched metastatic cancer patients with progressive disease were enriched using Ficoll density gradient centrifugation and detected by pan-keratin/Jagged1/CD45 immunofluorescent staining. RESULTS: Jagged1 expression was detected in 50% of 228 tumors. Jagged1 expression was correlated with higher tumor grade ( P = 0.047), vascular invasion ( P = 0.026), luminal B subtype ( P = 0.016), overexpression of Her-2 ( P = 0.001), high Ki-67 expression ( P = 0.035), and aldehyde dehydrogenase 1 (ALDH1) positivity ( P = 0.013). Jagged 1 expression indicated shorter disease-free survival (DFS) ( P = 0.040) and metastasis-free survival ( P = 0.048) in lymph node–negative breast cancer for which it was the only independent predictor of DFS (multivariate analysis, P = 0.046). Tumors characterized by the strongest Jagged1 staining intensity (7.5% of cases) correlated with lymph node positivity ( P = 0.037), metastatic relapse ( P = 0.049), and higher number of disseminated tumor cells in bone marrow aspirates ( P = 0.041). Twenty-one unmatched metastatic breast cancer patients with progressive disease were positive for CTCs, and 85.7% of the CTCs also expressed Jagged1. The presence of Jagged1(+) CTCs was significantly associated with shorter progression-free survival in patients treated with bisphosphonates ( P = 0.013). CONCLUSIONS: Jagged1 expression characterizes more aggressive breast carcinoma and might be involved in tumor cell dissemination, metastatic progression, and resistance to bone-targeting therapy in breast cancer patients.